Adversários face a face: uma análise da campanha negativa promovida por Dilma Rousseff e Aécio Neves no facebook durante as eleições de 2014 - Sousa, Ícaro Joathan de (2015)
This research aims to understand the promotion strategies of the negative campaign carried out by the two main candidates running for the Presidency of the Republic in Brazil during the pre-campaign, campaign, and post-campaign periods in 2014 – Dilma Rousseff (PT) and Aécio Neves (PSDB) – on Facebook. Such election was marked by a fierce dispute in the polls, and also by an aggressive attitude between those candidates in the several communication means – with special emphasis on the digital media. To do the research, all the posts published in the official fan pages of the two candidates running for Planalto Palace were collected between April 6 and November 2, 2014, which corresponds to the period officially established by the Electoral Superior Court (TSE), encompassing three months before the elections and one week immediately after. Through the techniques of content analysis and discourse analysis, only the posts classified under the “negative campaign” category are considered for the research, and obtained by checking the posts that presented information with the purpose or potential to negatively affect the image of the rivals. Then, the messages are sorted out based on the adaptation of categorizations of Kaid and Johnston (1991), Klotz (1998), Lourenço (2007, 2009), and Borba (2012a, 2012c, 2015). The classification checks the frequency; the author and the target of criticism; the type of resource used in the publication; the focus of the attacks; and the rhetoric appeal used by the competitors. At the end of the research, a mapping of the usage forms of the negative ads in such social network site is presented, which indicates as the main results that the attacks on Facebook were more frequent than in the free electoral advertisements on TV; that Dilma and Aécio had each other as preferred targets; that both of them used multimedia resources in their criticism, which was predominantly of political nature, and the credibility of the sources appeal.